2020
DOI: 10.3390/nu12082186
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fermentation of Cowpea (Vigna unguiculata) Flour Improves the Nutritive Utilization of Indispensable Amino Acids and Phosphorus by Growing Rats

Abstract: Cowpea (Vigna unguiculata) is among the most cultivated legumes, with interesting agronomic and environmental properties, and great potential as a nutritious food. The nutritional value of cowpea can be improved by technological processing. In this study, we showed that natural fermentation improved bioavailability of protein, amino acids, and dietary essential minerals from cowpea in growing rats, thus strengthening its potential value as functional food or food supplement. Forty Wistar albino rats (48 ± 1.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Among all the assayed minerals, potassium, phosphorus, magnesium and calcium were abundant in the flour samples. Previous studies also showed that raw cowpea and quinoa flours are good sources of macrominerals (Marmouzi et al, 2015;Kapravelou et al, 2020). The sourdough flours displayed significantly (P ≤ 0.05) higher levels of the minerals and strongly correlated with their higher ash contents (4.17% and 4.42%, Table 2).…”
Section: Mineral Composition Of the Flour Samplesmentioning
confidence: 64%
See 3 more Smart Citations
“…Among all the assayed minerals, potassium, phosphorus, magnesium and calcium were abundant in the flour samples. Previous studies also showed that raw cowpea and quinoa flours are good sources of macrominerals (Marmouzi et al, 2015;Kapravelou et al, 2020). The sourdough flours displayed significantly (P ≤ 0.05) higher levels of the minerals and strongly correlated with their higher ash contents (4.17% and 4.42%, Table 2).…”
Section: Mineral Composition Of the Flour Samplesmentioning
confidence: 64%
“…Among all the assayed minerals, potassium, phosphorus, magnesium and calcium were abundant in the flour samples. Previous studies also showed that raw cowpea and quinoa flours are good sources of macrominerals (Marmouzi et al ., 2015; Kapravelou et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mineral content ranged from 1.97 to 2.69 mg/100 g for calcium, 3.23 to 3.90 mg/100 g for magnesium, 205.53 to 223.30 mg/100 g for sodium, 0.80 to 1.23 mg/100 g for zinc, 1071.15 to 1152.62 mg/100 g for potassium and 0.62 to 1.06 mg/100 g for phosphorus. Cowpea has shown great potential for production of fermented yoghurt-like food products with improved bioavailability of nutrients [13,14]. Cowpea is rich in phenolic acids such as benzoic and cinnamic acid derivatives that are associated with antioxidant properties [15].…”
Section: Introductionmentioning
confidence: 99%